Performance-Based Navigation and Airspace Safety in ASEAN: A Comparative Quantitative Analysis - Quirina Ariantji Patrisia Mintje; Ariyono Setiawan; Ahmad Bahrawi; Deshinta Arrova Dewi (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2025)
This study aims to evaluate the impact of Performance-Based Navigation (PBN) implementation on airspace safety across ASEAN countries. Amid growing aviation traffic and the International Civil Aviation Organization (ICAO) push for harmonized air navigation strategies, ASEAN's PBN readiness varies significantly, warranting a regional assessment. Guided by the International Civil Aviation Organization (ICAO) Global Aviation Safety Plan (GASP) and Doc 9613 PBN Manual, this research investigates how integrating advanced navigation procedures and aligning policies contribute to improved safety outcomes. A comparative quantitative analysis was conducted using secondary data from 11 ASEAN countries between 2009 and 2023. Key variables include the PBN Coverage Index, Fleet RNAV Capability, Policy Alignment, and Safety Risk Index. Statistical methods included descriptive statistics, Pearson correlation, OLS regression, ANOVA, and hierarchical clustering. Regression results reveal that policy alignment with ICAO standards significantly reduces safety risk (p < 0.05), while higher PBN coverage shows a strong negative correlation with risk levels (r = –0.80). ANOVA indicates statistically significant differences in safety performance across readiness levels. Clustering analysis distinguishes three country groups, with Indonesia, Singapore, and Thailand leading in PBN readiness. The findings highlight the need for harmonized regional aviation strategies, particularly in countries with limited infrastructure, such as Timor-Leste. Strengthening regulatory compliance and technological adoption is essential for safety enhancement. This study offers integrated multi-method analysis of PBN implementation and safety outcomes in ASEAN, contributing empirical insights for aviation policymakers and ICAO stakeholders.